2021
DOI: 10.1128/aem.02418-20
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Agricultural Factors Influence Escherichia coli Survival in Soil and Transfer to Cucumbers

Abstract: Biological soil amendments of animal origin (BSAAO) increase nutrient levels in soils to support production of fruits and vegetables. BSAAOs may introduce or extend survival of bacterial pathogens which can transfer to fruits and vegetables to cause foodborne illness. Escherichia coli survival over 120 days in soil plots (3m2) covered with (mulched) or without plastic mulch (not mulched), amended with either poultry litter, composted poultry litter, heat treated poultry pellets, or chemical fertilizer and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The agricultural soil may naturally contain pathogenic bacteria or receive them during soil amendment using animal manure [ 28 ]. Soil amendment with animal manure increases crop yield, but it can potentially increase the spread of foodborne pathogens and ARGs in the environment [ 29 , 30 , 31 ]. Therefore, the USA Food and Drug Administration has recently limited the use of antimicrobials on farms in the USA due to the growing impact of antibiotic resistance in clinical practice and to reduce the selection pressure on the emergence of resistance bacteria [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The agricultural soil may naturally contain pathogenic bacteria or receive them during soil amendment using animal manure [ 28 ]. Soil amendment with animal manure increases crop yield, but it can potentially increase the spread of foodborne pathogens and ARGs in the environment [ 29 , 30 , 31 ]. Therefore, the USA Food and Drug Administration has recently limited the use of antimicrobials on farms in the USA due to the growing impact of antibiotic resistance in clinical practice and to reduce the selection pressure on the emergence of resistance bacteria [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we did not measure the concentration of antibiotics in the collected samples, but different studies showed that antimicrobials were detected in agricultural soil amended with animal manure (Gros et al., 2019 ; Srichamnong et al., 2021 ). Thus, soil amendment with animal manure can potentially increase the selection and spread of resistant bacteria (Litt et al., 2021 ). In this study, E. coli isolates from soil showed a high rate of resistance to ampicillin, gentamicin, kanamycin, and sulfisoxazole, compared to manure and vegetable samples.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella enterica levels in water may be affected by agricultural practices such as using untreated manure as organic fertilizer, contributing to contaminated runoff to water bodies [48]. Other reports have shown that soil runoff containing organic fertilizers (heat-treated poultry pellets) can support Salmonella growth in water [49], and that soils amended with synthetic and heat-treated or composted organic fertilizers were contaminated with Salmonella as well [50]. In addition to the agricultural land use proximate to MA05, there was also relatively high wetlands land cover (17.7%), which may support wildlife (including avian, amphibian, and reptile populations), and these animals are known contributors to the S. enterica burden in this stream [51,52].…”
Section: Empirical Orthogonal Functionsmentioning
confidence: 99%